Penilaian Tingkat Kapabilitas Proses Akuisisi Pengembangan Sistem Informasi Menggunakan CMMI For Acquisition (CMMI-ACQ) Versi 1.3 (Studi Kasus: Dinas Komunikasi dan Informatika Kabupaten Tulungagung) - Ulya Nuzulir Rohmah; Aditya Rachmadi; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika (Diskominfo) Tulungagung is a government institution of Tulungagung that has a role to build a government based on information technologycalled e-government. In order to realizing e-government, Diskominfouse the ability of suppliers to develop their information system. However, in its implementation there are a lot of management error in defining requirements that makes project out of schedule. The purpose of this research is to assess the capability level of the acquisition process of information system development by adjusting the problems and objectives of improvement to the project roadmap according to CMMI for Acquisition 1.3 framework. The results of this research are the capability level of each process area appraised. The process of appraisal using Standard CMMI Appraisal Method for Process Improvement (SCAMPI) class C.The data used in this research were collected using interview and document tracking. There are 6 process area assessed in this research based on CMMI project roadmap. Based on the results of the assessment, it was found that only process area of Agreement Management that is at capability level 1, performed. While the other 5 process areas in project roadmap are at capability level 0, incomplete.